Analyzing Student Needs at Darullughah Wal Karomah Islamic Boarding School Through Maslow’s Hierarchy of Needs - Anshori, Muhammad Mukhlis; Muzekki, Taufikur Rohman; Athi'ullah, Ibnur Rijal; Ardianti, Vika; Nasikhah, Wulan Roudhotul (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This article discusses the role of Islamic boarding schools in achieving quality education by fulfilling students' basic needs by referring to Maslow's Hierarchy of Needs theory. This research method uses a qualitative approach with a type of field research. Data was obtained from two main sources, namely primary data and secondary data. Primary data, especially from the Darullughah Wal Karomah Islamic Boarding School. Data collection techniques include interviews, observation, and documentation, with data analysis based on the Miles and Huberman approach.The research results show that Islamic boarding schools meet the basic needs of students: (1) physiological with a canteen, cooperative, bedroom, and barber shop; (2) a sense of security through counseling guidance, physical and spiritual security; (3) affection from caregivers; (4) appreciation through annual activities and prizes; (5) support for potential development through LPBA, LPBI, and extracurricular activities. The research results show that Islamic boarding schools have met the needs of students based on Abraham Maslow's perspective, starting from physiological needs, a sense of security, social needs, and self-actualization.